ON THE POSSIBILITIES OF USING VARIOUS PLASTICS TYPES FOR 3D PRINTING OF SUBMERGED MARINE DEVICES PARTS - Гайша, Олександр; Гайша, Олена (Modern engineering and innovative technologies, 2024)
The possibility of using 3D printing technology for the production of parts for the underwater devices operating in the marine environment is considered. It is substantiated that this technology can be effective for small-sized (about meters) parts of com